Dopamine Modulation of Reunion Behavior in Short and Long Term Marmoset Pairs - Carp, Sarah B.; Taylor, Jack H.; Womack, Stephanie L.; French, Jeffrey A. (Frontiers in Ecology and Evolution, 2018)
One major neurobiological substrate regulating social processes is dopamine (DA). DA is implicated in social behavior in species as diverse as fish and birds, and has an established role in regulating relationships between mates in socially monogamous rodents. Marmoset monkeys display traits associated with social monogamy including high rates of affiliation, biparental care, distress upon separation, and aggression toward strangers; several of these behavioral patterns change throughout the development of relationships. This temporal change may represent changing demands, as pairs are likely to jointly face new experiences (e.g., parenthood) throughout pairing. We investigated the role of DA and pairing length on social behavior during reunion after separation from the partner. Marmosets were removed from their home environment and treated with agonists and antagonists for the D1 and D2 receptor subtypes. They were exposed to a novel environment containing an opposite-sex stranger and the pair mate, and then reunited with their mate in the home enclosure. Marmosets in long term pairs exhibited higher levels of food sharing during reunion than marmosets in short term pairs, with females in long term pairs sharing food more than males; no sex difference were observed in short term pairs. Subjects in short term pairs spent more time grooming their mate than receiving grooming during reunion, while marmosets in long term pairs displayed similar amounts of both initiated and received grooming. DA treatment altered pair-level behavior. When females received either a D2 agonist or antagonist, short term pairs spent less time in proximity, compared to when males received the same treatments. In long term pairs, treatment of females with either a D1 agonist or antagonist resulted in pairs spending less time in social proximity than when males were treated. These findings suggest that the function of the DA system in mate behavior may be similar between rodents and primates, with the D1 system modulating the expression of behavior in long term pairs and the D2 system regulating behavior in short term pairs. Furthermore, these results supplement a large body of work suggestive of deep evolutionary roots of the DA system in regulating social behavior.